PELAYANAN FISIOTERAPI PREVENTIF DAN PROMOTIF PADA NYERI PUNGGUNG BAWAH DENGAN PENDEKATAN ERGONOMI DI WILAYAH PUSKESMAS JATIRAHAYU KECAMATAN PONDOK MELATI KOTA BEKASI - Achwan Achwan; Yusuf Nasirudin (Jurnal Pengabdian Masyarakat Fisioterapi dan Kesehatan Indonesia, 2023)
LBP complaints among tailors often arise due to their jobs require them to sit for long periods of time quite a long time. This sitting position is a high risk factor disruption occurs LBP. Work attitudes and work facilities need to be considered because if a work attitude that is not ergonomic is maintained at the same time long enough can result in LBP. Maintain a healthy lifestyle such as regular physical activity, maintaining body weight and getting checked Regular health is an important thing that must be done by tailors so that they do not suffer from health problems, especially LBP. The purpose of this PkM is to increase knowledge about prevention and promotion of handling LBP with an ergonomic approach to tailors in the working area of the Puskesmas Jatirahayu Village, Pondok Melati District, Bekasi City. The method for implementing Community Services activities is socialization and identification, counseling and education on physical exercise in the community. Before and after the activity is carried out, an evaluation will be carried out in the form of: administering questionnaires to obtain information related to LBP complaints experienced. The results achieved in this Community Services are establishment collaboration with the Jatirahayu Community Health Center and the participants, it was implemented counseling and physical training as well as carrying out evaluations of Community Services activities. Conclusion There is an increase in knowledge regarding preventive and promotive handling of LBP with an ergonomics approach for tailors in the working area of ​​the Jatirahayu Village Health Center, Pondok Melati District Bekasi City.